Mortality, fertility and old age care in a two-sex growth model - Leif Andreassen (Statistics Norway, Research Department, 2004)
The paper discusses the importance of decreasing mortality in explaining demographic change over the last century. A two-sex overlapping generations model is used where care both for children and the elderly is modeled. Assuming that the main costs of care are tied to time use (and thereby fairly invariant to income changes), the paper illustrates how exogenous changes in mortality, the cost of children and the bargaining power of women can explain fluctuations in both the level and timing of births. The interaction between declining mortality and the expansion of care for the elderly is of special importance. As a consequence, mortality affects fertility differently according to how much the government sector has expanded and how much human capital has been accumulated. At an early development stage, when public care is little developed, the effect of decreasing mortality on fertility is found to be positive, while at a later stage, with higher levels of public care, the effect is found to be negative.
Keywords: D1; D9; J1; 330; mortality; fertility; old age care; olg